Pengaruh Work-Life Balance dan Komitmen Organisasi Terhadap Kinerja Karyawan di PT. Telkom Witel Jatim Surabaya Selatan - Zahara Luthfiyani (BIMA : Journal of Business and Innovation Management, 2019)
PT. Telkom Witel Jatim Surabaya Selatan is telecommunication company in southern part of the Surabaya. The factor of human resources as the driving force of the company in advancing the company needs an increase in employee performance, so companies need to focus on the conditions of their employees. This study aims to know and explain the effect of work-life balance and organizational commitment either partially or simultaneously on employee work performance, This study is a quantitative study, with this type of research using causal research, namely the form of causal relationships. This number of 60 respondents by using simple random sampling. The result of this study shows that: (1) Work-life balance partially has a positive significant effect on employee performance, which tcount 3,150 > t table 1,671 with the significant value is 0,003. (2) Organizational commitment partially has a positive significant effect on employee performance, which t count 3,539 > t table 1,671 with the significant value is 0,001. (3) Work-life balance and organizational commitment simultaneously has an effect on employee performance, which F count 28,780 > F table 3,16 and the significant value is 0,000.